Evolusi Studi Tentang Risk Management dan Organisasi: Analisis Bibliometrik - Aisyah, Vella Nur; Sanjaya, Febry Prima; Usman, Indrianawati; Alamsyah, Andi Indra Saputra (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
This study aims to evaluate trends or developments in studies on risk management and organizations by searching published documents. The method that is maximized is by carrying out bibliometric analysis.. The method that is maximized is by carrying out bibliometric analysis. The data source comes from the Scopus database. The analysis tool used is Vosviewer. The main findings of this research indicate a significant growth in the number of publications related to risk management and organizations over the last few decades. The United States leads in the number of publications. The frequently cited documents in this study also provide insight into the most relevant topics in this research, including strategic planning, risk assessment, risk management, and more. However, several themes still need to be explored further, such as the role of accounting management and the impact of risk management on organizational performance. The implication of this study is the importance of better awareness and understanding of risk management in modern organizations.